2005
DOI: 10.1021/ja0509073
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Confirmation of a Pentavalent Phosphorane in Complex with β-Phosphoglucomutase

Abstract: This communication reports the X-ray crystal structure of the alpha-d-galactose-1-phosphate complex with that of Lactococcus lactis beta-phosphoglucomutase (beta-PGM) crystallized in the presence of Mg2+ cofactor and the enzyme-to-phosphorus ratio determined by protein and phosphate analyses of the crystalline complex. The 1:1 ratio determined for this complex was compared to the 1:2 ratio determined for the crystals of beta-PGM grown in the presence of substrate and Mg2+ cofactor. This result verifies the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 8 publications
(14 reference statements)
7
59
0
Order By: Relevance
“…The electron density map is also consistent with a TS analogue (TSA) formed from a five-coordinate magnesium surrounded by two oxygen and three fluoride ligands (MgF 3 -TSA) that mimics the phosphoryl group in flight (12,13). The crystallization buffer needs to contain magnesium and fluoride ions for crystals to form (14,15), so all of the components necessary for the formation of the MgF 3 -TSA are available. Furthermore, ab initio quantummechanical calculations indicate that MgF 3 -TSA is stable, whereas INT is not and spontaneously rearranges to a phosphate monoester covalently bound to either the substrate or the enzyme, as would be expected of a transition state (16).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…The electron density map is also consistent with a TS analogue (TSA) formed from a five-coordinate magnesium surrounded by two oxygen and three fluoride ligands (MgF 3 -TSA) that mimics the phosphoryl group in flight (12,13). The crystallization buffer needs to contain magnesium and fluoride ions for crystals to form (14,15), so all of the components necessary for the formation of the MgF 3 -TSA are available. Furthermore, ab initio quantummechanical calculations indicate that MgF 3 -TSA is stable, whereas INT is not and spontaneously rearranges to a phosphate monoester covalently bound to either the substrate or the enzyme, as would be expected of a transition state (16).…”
supporting
confidence: 52%
“…5). However, the published inhibition study was conducted under the unusual conditions of a 2-fold excess of intermediate ␤-G16BP (200 M) to substrate ␤-G1P (100 M) (15). When we repeated our experiments in the presence of high concentrations of ␤-G16BP, we also observed that even 10 mM fluoride did not inhibit the reaction (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Recently, a crystal structure of an intermediate of an enzyme-catalyzed phosphoryl transfer reaction was reported (20). This intermediate was analyzed as a pentacovalent phosphate structure, but there is considerable controversy concerning this interpretation (21)(22)(23).…”
mentioning
confidence: 99%
“…The rate and equilibrium for phosphorylation of the active site Asp8 by G16bisP are examined. A model for PGM catalysis is proposed that is based on cycling of the enzyme between the open and closed conformations observed in the reported PGM X-ray crystal structures (6,(12)(13)(14). lactis -phosphoglucomutase ( PGM) was prepared according to a published procedure (16).…”
mentioning
confidence: 99%